PENDIDIKAN SEBAGAI PROSES SOSIAL BUDAYA BAGI PESERTA DIDIK - Suryati, Suryati; Ernawati, Eli; Ubabuddin, Ubabuddin (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2024)
Education cannot be separated from the social and cultural context in which it operates. This research is a literature research with content analysis. The results of the study state that education is a cultural heritage from generation to generation so that the identity of society is better preserved, education can shape a person better before he is educated. It is through education that good values are taught to a person, so that he knows what is good, and what is bad. Among the solutions that need to be taken into account is how efforts in shaping the personality and behavioral changes of individuals or communities. Cultural education is one of the solutions in overcoming the problems that occur in the world of education, especially the problem of rampant brawls and riots and demonstrations that have occurred lately. Education consisting of formal education and non-formal education is an important element in creating education with cultural nuances. Thus, education with cultural nuances is expected to produce educational products that uphold cultural values and personality values.